Religiosity and Sense of Meaning in Life among Undergraduate Students - Vialita Fitria Survanta Idham; Nurul Wardhani (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2026)
Meaning in life is a fundamental element that shapes how individuals interpret their world. Religion serves as one of the primary sources of meaning in life. This study aimed to examine the relationship between religiosity and sense of meaning in life during emerging adulthood. A non-experimental correlational design with quantitative primary data was employed, collected through the CRS-15 TII questionnaire and the Meaning in Life Questionnaire. Convenience sampling was utilized; however, participant representativeness was enhanced through probability sampling across various faculties at Universitas Padjadjaran. A total of 71 respondents were recruited through questionnaires distributed via Google Form, Line, and WhatsApp. Results indicated a substantial relationship between religiosity and the presence of meaning, but no significant association with the search for meaning. The majority of respondents demonstrated high scores in religiosity, presence of meaning, and search for meaning. These findings underscore the importance of religiosity as a source of meaning in life during emerging adulthood and open avenues for further research and the development of faith-based programs.